Ratio Legis Pengaturan Rehabilitasi Warga Binaan di Lembaga Pemasyarakatan Sebagai Instrumen Pengurangan Residivisme Tindak Pidana Narkotika - Musahib, Abd Razak; Warka, Made; Mangunsong , Frans Si (Riviera Publishing, 2025)
The ratio legis of rehabilitation regulation in Indonesian positive law reflects a shift in the criminal paradigm from a repressive system to a restorative and rehabilitative approach. This study is important to test the suitability of legal objectives (rechtsidee) with the implementation of applicable norms, as well as assess the extent to which rehabilitation arrangements can function as a legal instrument in reducing recidivism rates in narcotics offenders. Law Number 35 of 2009 concerning Narcotics and Law Number 22 of 2022 concerning Corrections have regulated rehabilitation for perpetrators of narcotics crimes. However, implementation in the field faces obstacles such as limited facilities, human resources, and post-rehabilitation monitoring mechanisms. Permenkumham No. 12 of 2017 concerning the Implementation of Medical and Social Rehabilitation for Prisoners and Prisoners of Narcotics Abusers Medical Rehabilitation is intended for narcotics addicts who are still experiencing physical dependence and need medical treatment. Rehabilitation arrangements in correctional institutions (Lapas) are based on several national regulations that regulate how inmates, especially those involved in narcotics cases, receive coaching and recovery so that they do not return to commit similar crimes (recidivism). Rehabilitation as an instrument of recidivism reduction has a strong rational basis, because an effective rehabilitation program is able to improve behavior, strengthen self-control, and equip inmates with life skills. Thus, they have a greater chance of living a productive life after being free and not falling back into narcotics abuse. However, the implementation of rehabilitation in prisons still faces a number of challenges, such as limited facilities, professional personnel, and the lack of follow-up programs (aftercare) after the prisoners are released. This hinders the effectiveness of rehabilitation in reducing recidivism.